Use of statins as a form of protection against age-related macular degeneration (AMD) - Drobek-Słowik, Monika; Karczewicz, Danuta; Safranow, Krzysztof; Jakubowska, Katarzyna; Chlubek, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To evaluate the association between use of lipid-lowering medications and occurrence of age-related macular degeneration (AMD). Material and methods: 91 patients with dry and 55 with exudative type AMD diagnosed with fundus fluorescein angiography were included to the study. Control group for the study Consisted of 68 participants without AMD. Data regarding use of cholesterol-lowering medications were collected with details. Results: In control group we noted significantly higher percentage of statin users compared to patients with AMD. Conclusions: Use of statins may be a protective factor against age-related macular degeneration.